Methods of Islamic Education in the Qur’an and Sunnah: Pedagogical Approaches and Educational Values - Andewi Suhartini; Dicky Alfian Nur Rachman; Sheila Mafaizah; Siti Sutiawati; Khoiruddin Manurung; Farhan Fauzan Abdurrahman (Tarbawiyah Jurnal Ilmiah Pendidikan, 2026)
Islamic education aims to cultivate individuals who possess faith, knowledge, and noble character. However, contemporary educational practices often emphasize cognitive achievement while paying less attention to the pedagogical processes through which Islamic values are internalized. Although many studies have identified educational methods in the Qur’an and Sunnah, most remain descriptive and focus on individual methods, with limited efforts to integrate them into a comprehensive pedagogical framework relevant to contemporary educational theories. This study aims to analyze Islamic educational methods derived from the Qur’an and Sunnah through pedagogical perspectives and an examination of their educational values. Employing a qualitative descriptive design with a literature review approach, data were collected from the Qur’an, Hadith, and relevant scholarly literature and analyzed using content analysis. The findings reveal eight major Islamic educational methods: storytelling, exemplary conduct, dialogue, lecturing, targhib wa tarhib, parables, demonstration, and repetition (tikrar). These methods possess strong epistemological foundations and are compatible with contemporary pedagogical theories, including Narrative-Based Learning, Social Learning Theory, Constructivism, and Experiential Learning. The study concludes that the integration of these methods forms a holistic pedagogical framework that supports the internalization of tawhid values and spiritual awareness beyond knowledge transmission. This study contributes an integrative conceptual synthesis linking Islamic educational methods, contemporary pedagogical theories, and Islamic educational values.